Effect of Aqueous Extract from Descurainia sophia (L.) Webb ex Prantl on Ventricular Remodeling in Chronic Heart Failure Rats. (13th June 2018) - Luo, Ying; Sun, Zhiqiang; Hu, Pengfei; Wu, Yuanhong; Yu, Weiwei; Huang, Shuwei
Abstract : Objective . Descurainia sophia (L.) Webb ex Prantl (DS) is a traditional Chinese medicine. Our current study was to evaluate the effect of DS on ventricular remodeling in chronic heart failure (HF) rats and its underlying mechanism. Methods . The rat chronic heart failure model induced by suprarenal abdominal aortic coarctation surgery. The survival rats were randomly divided into 3 groups: the sham group (n=6), the HF group (n=6), and the HF+DS group (n=6). After 3 months of drug intervention, we examined the effects of DS by Sirius Red staining, electron microscopy, echocardiography, hemodynamic measurement, and TUNEL and explored the underlying mechanism by Western blotting. Results . We found that rats treated with DS showed improved cardiac function and less tissue damage compared to untreated group. Additionally, DS could reduce the cardiomyocytes apoptosis, decrease the ratio of Bax/bcl-2 and Caspase-3 expression, and enhance the phosphorylation of Akt protein expression. Conclusion . Our study suggested that rats treated with DS after suprarenal abdominal aortic coarctation surgery showed attenuated cardiac fibrosis and apoptosis, and the protective effect may be correlated with the activation of PI3k/Akt/mTOR dependent manner.